Influence of Different Carrier Gases, Temperature, and Partial Pressure on Growth Dynamics of Ge and Si Nanowires - Nicolas Forrer; Arianna Nigro; Gerard Gadea; Ilaria Zardo (Nanomaterials, 2023)
The broad and fascinating properties of nanowires and their synthesis have attracted great attention as building blocks for functional devices at the nanoscale. Silicon and germanium are highly interesting materials due to their compatibility with standard CMOS technology. Their combination provides optimal templates for quantum applications, for which nanowires need to be of high quality, with carefully designed dimensions, crystal phase, and orientation. In this work, we present a detailed study on the growth kinetics of silicon (length 0.1–1 <semantics>μ</semantics>m, diameter 10–60 nm) and germanium (length 0.06–1 <semantics>μ</semantics>m, diameter 10–500 nm) nanowires grown by chemical vapor deposition applying the vapour–liquid–solid growth method catalysed by gold. The effects of temperature, partial pressure of the precursor gas, and different carrier gases are analysed via scanning electron microscopy. Argon as carrier gas enhances the growth rate at higher temperatures (120 nm/min for Ar and 48 nm/min H<semantics>2</semantics>), while hydrogen enhances it at lower temperatures (35 nm/min for H<semantics>2</semantics> and 22 nm/min for Ar) due to lower heat capacity. Both materials exhibit two growth regimes as a function of the temperature. The tapering rate is about ten times lower for silicon nanowires than for germanium ones. Finally, we identify the optimal conditions for nucleation in the nanowire growth process.